1994
DOI: 10.1177/000992289403300304
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Function in Malnourished Children

Abstract: The cardiovascular status of severely malnourished children was characterized before, during, and after nutritional rehabilitation. In most children with third-degree malnutrition, cardiac mass was decreased on admission to the hospital and recovered subsequent to nutritional therapy. All children had echocardiographic and Doppler measurements indicative of impaired ventricular function which significantly improved during the course of hospitalization, as evidenced in part by the change in fractional shortenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
41
2

Year Published

1997
1997
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 15 publications
7
41
2
Order By: Relevance
“…Also, Phornphatkul et al (1994) concluded that the children with primary third-degree malnutrition not only have cardiac wasting, but also inherent ventricular dysfunction as the result of severe malnutrition that responds to nutritional therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, Phornphatkul et al (1994) concluded that the children with primary third-degree malnutrition not only have cardiac wasting, but also inherent ventricular dysfunction as the result of severe malnutrition that responds to nutritional therapy.…”
Section: Discussionmentioning
confidence: 99%
“…These may variably influence the cardiac function (Kothari et al, 1992). In addition, Phornphatkul et al (1994) reported that children with malnutrition not only have cardiac muscle wasting but also have inherent ventricular dysfunction as a result of severe malnutrition that responds to nutritional therapy. It has been reported that myocardial dysfunction either in the form of cardiac arrhythmia or heart failure are among the causes of death in kwashiorkor (Olowonyo et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…All these pathological changes lead to disturbed cardiac functions in the electrical activity of the heart that may be reflected in the electrocardiogram (ECG). 5 However, studies on electrocardiographic and echocardiographic changes in Malnutrition are scant. To a great extent, SAM is one of the leading causes of mortality and morbidity in the pediatric population in developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…It remain unresolved, however, if these abnormalities are primary phenomenon of malnutrition or secondary to other abnormalities commonly associated with severe malnutrition, such as sepsis. [3][4][5] The heart atrophies during starvation, but controversy persist as to whether the atrophic heart with PEM functions normally or demonstrates left ventricular dysfunction.…”
Section: Introductionmentioning
confidence: 99%